2003
DOI: 10.1590/s0036-46652003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin at the late stage of leptospirosis: a randomized controlled trial

Abstract: There is evidence that an early start of penicillin reduces the case-fatality rate of leptospirosis and that chemoprophylaxis is efficacious in persons exposed to the sources of leptospira. The existent data, however, are inconsistent regarding the benefit of introducing penicillin at a late stage of leptospirosis. The present study was developed to assess whether the introduction of penicillin after more than four days of symptoms reduces the in-hospital case-fatality rate of leptospirosis. A total of 253 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 25 publications
2
64
0
4
Order By: Relevance
“…44,45 Some reports, however, suggest that penicillin therapy did not provide better clinical outcome in patients with leptospirosis and acute kidney injury, mainly after at least four days of symptomatic disease. 12,46 In the present study, Penicillin G was administered in 131 (65%) of the patients. The majority of these patients, in the last decade, promptly received penicillin as soon as they were admitted in the hospital.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…44,45 Some reports, however, suggest that penicillin therapy did not provide better clinical outcome in patients with leptospirosis and acute kidney injury, mainly after at least four days of symptomatic disease. 12,46 In the present study, Penicillin G was administered in 131 (65%) of the patients. The majority of these patients, in the last decade, promptly received penicillin as soon as they were admitted in the hospital.…”
Section: Discussionmentioning
confidence: 91%
“…Costa et al 11 found 14.2% of death among severe leptospirosis cases. Costa et al 12 reported 9% of nonsurvivors among 253 patients. In the present study, death occurred in 15.4% of cases, and the majority of them were due to pulmonary bleeding.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Consensus about the use of antibiotics for treating leptospirosis still lacks. [44][45][46][47][48] A recent meta-analysis has not found sufficient evidence to indicate the use of antibiotics in leptospirosis; however, it concluded that antibiotic therapy in that disease seemed to have more benefits than drawbacks. 44 A recent experimental study has assessed the expression of the NHE3 of the proximal tubule and of the NKCC2 in hamsters with leptospirosis treated or not with ampicillin.…”
Section: Treatment Antibiotic Therapymentioning
confidence: 99%